Science, information, and policy interface for effective coastal and ocean management - MacDonald, Bertrum H. (CRC Press, 2016)
This book provides a timely analysis of the role that information-particularly scientific information-plays in the policy-making and decision-making processes in coastal and ocean management. It includes contributions from global experts in marine environmental science, marine policy, fisheries, public policy and administration, resource management.